"Viewed as Equals": The Impacts of Library Organizational Cultures and Management on Library Staff Morale. Issue 2 (17th February 2022) - Glusker, Ann; Emmelhainz, Celia; Estrada, Natalia; Dyess, Bonita
Abstract: The literature on academic librarian morale is burgeoning, yet less attention has been paid to the workplace experiences of staff. This research team, which included library staff and librarians, conducted 34 structured online interviews with academic library staff across the United States. A theoretical model and interview findings are presented, which reveal the ways in which organizational culture, library hierarchies, and management style affect staff morale. Recommendations are offered, suggesting that, while change can present substantial challenges, efforts to address equity in compensation, provide professional growth opportunities, and create more collegial work environments are essential to improving staff morale.